Surveillance of Nitrofuran Metabolite Residue in Pacific White Shrimp (Litopenaeus vannamei) at Local Market in Bangkok - Natchamon Wangwibulkit; Aphacha Jindaprasert; Soraya Kerdpiboon; Adison Swetwiwathana (My University, 2023)
The study aimed to analyze nitrofuran metabolite residues in Pacific white shrimp (Litopenaeus vannamei) from the 5 local markets in Bangkok. The samples weighing from 9.20+0.79 to 31.00+0.67 g were analyzed for nitrofuran metabolites: 3-amino-2-oxazolidinone (AOZ), 3-amino-5-morpholinomethyl-2-oxazolidinone (AMOZ), 1-aminohydantoin (AHD) and semicarbazide (SEM) by using LC-MS/MS technique. The results showed that only SEM in the range 0.104-0.160 ug/kg was found. The correlation coefficient between weight and SEM showed the negative linearity (r = -0.6867). It was found that there were less SEM residues in large shrimps than small shrimps. Therefore, the size of white shrimp can be used as an index for purchasing shrimp that are safe for consumers.
Keywords: Litopenaeus; Semicarbazide; Nitrofuran; Residue (chemistry); Furazolidone; Pesticide Residue Analysis and Safety